Virtual Social Networking Hours: A Vital Personal and Professional Avenue for Connecting Pharmacy Leadership Educators - Gregory Zumach; Whitney D. Maxwell; Kerry K. Fierke (University of Minnesota Libraries Publishing, 2023)
The American Association of Colleges of Pharmacy (AACP) Leadership Development Special Interest Group (LD SIG) created a Virtual Social Networking Hour (VSNH). The VSNH explored pharmacy leadership educators' connections through discussing topics of interest that influence current teaching and scholarship practices. The VSNH also served to connect members in the LD SIG through informal networking, which was vital during a time when in-person connection was heavily restricted due to the COVID-19 global pandemic. The VSNH functioned as both a space for members to connect with LD SIG leadership and other members of the LD SIG and a tool to areas of leadership development the SIG should explore in future programming. Each of the four sessions included a skeleton structure that grew organically based on the conversations of the attendees. Common themes of scholarship, adaptation to a virtual landscape, leadership, and student-focused endeavors were interwoven across all four sessions. The VSNHs have since become an integral component in LD SIG Programming.